Pengaruh Tingkat Inflasi dan Laju Pertumbuhan Investasi terhadap Pendapatan Asli Daerah pada Kabupaten di Sumatera Selatan Tahun 2018-2020 - Sukmini Hartati; Indriani Indah Astuti; Indah Mellynna (Penerbit Goodwood, 2023)
Purpose: This study examines how regional original income in the cities of South Sumatra Province is partially and simultaneously affected by investment growth and inflation between 2018 and 2020.Purpose: This study examines how regional original income in the cities of South Sumatra Province is partially and simultaneously affected by investment growth and inflation between 2018 and 2020. Methodology/Approach: The analysis in this study was performed using panel data, which are a combination of cross-sectional and time-series data. Results/findings: According to the national development mission, which calls for the realization of an independent, prosperous, and united society based on Pancasila and the 1945 Constitution, economic growth is a strategy for improving the nation's standard of living. Involving local governments' use of natural resources and initiatives to increase products per capita. LGR is regional income that indicates a region's degree of independence. The presence of the LGR enhances the capacity of the region to explore and exploit its resources. Own-source revenue is negatively affected by the inflation rate, as demonstrated in this study. Meanwhile, the rate of investment growth has a positive impact on local revenue. Local revenue is positively impacted by both inflation and the investment growth rate simultaneously.